The distribution characteristics of aquaporin 4 antibody in patients with neuromyelitis optica and the relationship between aquaporin 4 antibody and oligoclonal bands - Hui-cong NIU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2014)
Objective To explore the distribution characteristics of aquaporin 4 (AQP4) antibody in serum and cerebrospinal fluid (CSF) of neuromyelitis optica (NMO) patients, and to analyze the relationship between AQP4 antibody and oligoclonal bands (OB) in CSF of NMO patients.  Methods Enzyme-linked immunosorbent assay (ELISA) and indirect immunofluorescence assay (IFA) were used to detect AQP4 antibody in serum and CSF of NMO and multiple sclerosis (MS) patients. Dynamic timed nephelometry was used to determine the levels of albumin and immunoglobulin G (IgG) in the CSF and serum. Isoelectric focusing (IEF) combined with immunofixation were used to detect OB in CSF. Western blotting was used to test whether AQP4 antibody existed in positive OB of NMO patients.  Results The mean concentration of AQP4 antibody in serum of NMO patients [8.94 (5.41, 11.93) ng/ml] was not significantly different from that of MS patients [7.34 (4.76, 12.00) ng/ml; Z = -0.510, P = 0.610); AQP4 antibody concentration in CSF of NMO patients [0.45 (0.42, 0.47) ng/ml] was higher than that of MS patients [0.41 (0.40, 0.41) ng/ml; Z = -2.359, P = 0.018]; AQP4 antibody concentration in serum of NMO patients was higher than that in CSF (Z = -3.702, P = 0.000). The positive rate of AQP4 antibody of NMO patients was higher than that of MS patients (5/7 vs 1/5), but there was no significant difference between the two (Fisher's exact test: P = 0.242). The concentration of AQP4 antibody in relapse phase [8.54 (5.32, 11.42) ng/ml] of NMO patients was not significantly different from that in remission phase [9.97 (5.41, 13.28) ng/ml; Z = -0.347, P = 0.728]. The positive rate of OB in NMO patients was significantly lower than that in MS patients (3/13 vs 10/14; Fisher's exact test: P = 0.021). No AQP4 antibody was detected in the IgG bands of OB positive NMO patients.  Conclusions AQP4 antibody concentration in serum of NMO patients was higher than that in CSF of NMO patients. It is of clinical significance to examine AQP4 antibody in CSF of NMO patients. Intrathecal IgG synthesis in NMO patients was lower than that in MS patients, and no AQP4 antibody was detected in the IgG bands of NMO patients with positive OB.   doi: 10.3969/j.issn.1672-6731.2014.09.011